Perspective of Fulfilling The Social Needs of Children Affected to The Mountain Semeru Eruption: Qualitative Study - Ira Rahmawati; Nuning Dwi Merina; Lantin Sulistyorini; Peni Perdani Julianingrum (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2024)
Indonesia is an archipelagic country located at the confluence of four tectonic plates and there are volcanic arcs along the islands of Sumatra-Java-Nusa Tenggara-Sulawesi. This condition causes Indonesia to be in a condition prone to natural disasters, especially volcanic eruptions. Disasters have a more serious impact on vulnerable groups. Semi-structured interviews were used to collect research data. Researchers collected demographic data at the research stage and then conducted direct interviews with research informants through in-depth interviews and Focus Group Discussion. A total of 24 participants were involved in this study which were taken using purposive sampling. The research was conducted on preschool and school aged children (3-12 years) who were affected by the eruption of Mount Semeru in Lumajang Regency, Indonesia. The Mount Semeru eruption disaster resulted in psychological problems in children because peer separation, behavior, and borderline personality disorder have been widely reported in volcanic eruption disasters. Good social support is an important aspect in the process of recovering children after a disaster. Rapid life changes encourage parents to adapt immediately to meet the needs of children.